2020
DOI: 10.4103/ijpsym.ijpsym_192_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Burnout among Undergraduate Medical Students - A Cross-sectional Survey

Abstract: Background: Burnout among medical students is important for its prevalence, consequences, and modifiable risk factors. Although there are studies on the topic across the globe, Indian studies are few in number. A prevalence estimate of burnout and its determinants among Indian medical graduates will keep us informed about the emotional and motivational factors hindering their professional growth. Methods: From a total of 500 students spanning 5 professional years, data could be collected from 375 students. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
3
15
0
4
Order By: Relevance
“…Academic stress had the second greatest total effect on burnout. This finding is consistent with previous studies that reported daily hassles positively correlated with burnout [ 63 ], academic stress negatively correlated with personal wellness [ 69 ], perceived stress associated with burnout [ 70 ], and academic stress as the most predictive of burnout [ 71 ]. These facts suggest that psychological wellbeing is negatively affected by high academic stress due to the demands of medical training [ 69 , 72 ].…”
Section: Discussionsupporting
confidence: 92%
“…Academic stress had the second greatest total effect on burnout. This finding is consistent with previous studies that reported daily hassles positively correlated with burnout [ 63 ], academic stress negatively correlated with personal wellness [ 69 ], perceived stress associated with burnout [ 70 ], and academic stress as the most predictive of burnout [ 71 ]. These facts suggest that psychological wellbeing is negatively affected by high academic stress due to the demands of medical training [ 69 , 72 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has been proposed, by some, that female medical students are at a high risk of burnout than their male counterparts. 14 Female students are more likely to suffer from stress factors than male medical students, 4 with more demands placed on them outside of the university. 8…”
Section: Discussionmentioning
confidence: 99%
“…The present study’s two-dimensional burnout is slightly lower than the Brazilian study (i.e., 44.9%), but a much higher rate is found for three-dimensional burnout (i.e., 26.4%). The prevalence of two-dimensional burnout is also reported to be 43.43% in Bahraini medical students [ 24 ], 35.9% in Brazilian medical internship students [ 25 ], 35.5% in Portugal medical students [ 26 ]; whereas using Copenhagen Burnout Inventory, 48.53% and 48.8% moderate to higher burnout is reported from Nepalese and Indian medical students, respectively [ 27 , 28 ]. Correspondingly, 28.4% three-dimensional burnout is reported in Thailand [ 29 ], whereas it is 10.3% and 25.9% for Brazilian and Portugal samples, respectively [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%